A 11‐Steps Total Synthesis of Magellanine through a Gold(I)‐Catalyzed Dehydro Diels–Alder Reaction. Issue 22 (12th January 2017) - McGee, Philippe; Bétournay, Geneviève; Barabé, Francis; Barriault, Louis
Abstract: We have developed an innovative strategy for the formation of angular carbocycles via a gold(I)‐catalyzed dehydro Diels–Alder reaction. This transformation provides rapid access to a variety of complex angular cores in excellent diastereoselectivities and high yields. The usefulness of this Au I ‐catalyzed cycloaddition was further demonstrated by accomplishing a 11‐steps total synthesis of (±)‐magellanine. Abstract : Building complexity : An efficient and operationally simple method for the formation of angular carbocycles via a gold(I)‐catalyzed dehydro Diels–Alder reaction is described. This transformation provides rapid access to complex angular cores in excellent diastereoselectivities. Its usefulness was further demonstrated by accomplishing a 11‐steps total synthesis of (±)‐magellanine.